An efficient data dissemination and handover scheme for vehicular ad hoc networks. (2017) - Shukla, Ravi Shankar; Tyagi, Neeraj; Gupta, Ashutosh; Dubey, Kamlesh Kumar
This paper presents a data dissemination and smooth handover scheme for vehicular ad hoc network. The data dissemination scheme is based on position-based routing class protocol and uses optimise forwarding to find forwarding node along the road pattern to deliver the data packets. The proposed routing algorithm ensures that all data packets are received with minimal delay and higher delivery ratio. A heterogeneous network architecture is proposed in this paper to support seamless mobility of mobile network. Each vehicle is provided with mobility through different internet server protocols (ISPs). The mobile router (MR) based handover scheme where MRs cooperatively receive packet destined for each other can provide no service disruption and significantly reduce packet loss during handover. It also makes the packet loss independent to handover latency. Simulation study shows the comparative performance of the proposed handover architecture in terms of throughput, handover latency service disruption time, packet loss and signalling overhead.